Geographical Variations in the Clinical Management of Colorectal Cancer in Australia: A Systematic Review - Crawford-Williams, Fiona; March, Sonja; Ireland, Michael J.; Rowe, Arlen; Goodwin, Belinda; Hyde, Melissa K.; Chambers, Suzanne K.; Aitken, Joanne F.; Dunn, Jeff (Frontiers in Oncology, 2018)
Background: In Australia, cancer survival is significantly lower in non-metropolitan compared to metropolitan areas. Our objective was to evaluate the evidence on geographical variations in the clinical management and treatment of colorectal cancer (CRC). Methods: A systematic review of published and grey literature was conducted. Five databases (CINAHL, PubMed, Embase, ProQuest and Informit) were searched for articles published in English from 1990 to 20162018. Final searches were conducted in November 2016. Studies were included if they assessed differences in clinical management according to geographical location; focused on CRC patients; and were conducted in Australia. Included studies were critically appraised using a modified Newcastle-Ottawa Scale. PRISMA systematic review reporting methods were applied. Results: Seventeen articles met inclusion criteria. All were of high (53%) or moderate (47%) quality. The limited evidence available may suggest that patients in non-metropolitan areas are more likely to experience delays in surgery, and are less likely to receive chemotherapy for stage III colon cancer and adjuvant radiotherapy for rectal cancer. Conclusions: The present review found limited information on clinical management across geographic regions in Australia and the synthesis highlights significant issues both for data collection and reporting at the population level, and for future research in the area of geographic variation. Where geographical disparities exist, these may be due to a combination of patient and system factors reflective of location. It is recommended that population-level data regarding clinical management of CRC be routinely collected to better understand geographical variations and inform future guidelines and policy.